Analisis Halal Supply Chain pada Usaha Mikro Kecil Menengah (UMKM) Makanan di Kota Bandung - Fauzan Aziz; Retno Setyorini; Yulia Nur Hasanah (ITB AAS INDONESIA Surakarta, 2021)
The halal supply chain is a concept where halal is not only seen as raw materials and production processes but also involves in the supply chain process. Indonesia, as the country with the largest Muslim population in the world, only has 20% of products that are halal certified, especially food Small Medium Enterprise (SMEs) in Bandung who most of which do not have halal certification. Therefore, this study aims to conduct a Halal Supply Chain Analysis of Small Medium Enterprise (SME) in Bandung. This research uses quantitative research methods with an associative descriptive approach. The sampling technique used simple random sampling with a total sample size of 94 food SMEs in Bandung. The data analysis technique used the Structural Equation Model-Partial Least Square (SEM-PLS) method. Based on the research results, the success factor of Halal Supply Chain has a positive and significant effect on the Implementation of Halal Supply Chain in Food SMEs in Bandung, with a contribution of 63.8%, and the remaining 36.2% is explained by other factors not examined. This shows that the implementation of the Halal Supply Chain will be successful if SMEs pay attention to each success factor of the Halal Supply Chain.